BIAYA TRANSAKSI DALAM PERSPEKTIF MANAJEMEN ADMINISTRASI (Studi Kuantitatif Layanan Instansi Pemerintah di Indonesia) - Nawi, Rusdin (Jurnal Ilmiah Administrasita, 2014)
The research aim to know the transaction cost in administration management prospective consist of the government cost and market cost with suitable the government service in administration management prospective. The number of respondent that use in this research about 337 respondents of staff from syariah banking institution in South Sulawesi Province. Analysis model which has been used in this research are quantitative descriptive and Structural Equation Model (SEM) by used AMOS programme. The result of government in applied of transaction cost have affect by the government cost suitable with routine cost, development cost, human resource cost and facility cost suitable with information, administration, operational and technology costs in applied the suitable of service with principle, accountable, leadership, productivity and service quality. The appointment of market cost have positive toward transaction cost for several activity or job program in government scope. The government instance have responsibility in appointment of transaction cost with give of propose planning suitable with need of government in applied of information, administration, operational and technology cost which affected toward suitable of service. Although the transaction cost in specific occured with the transaction cost particularly relate with cost transaction because the government cost require to suitable with transaction cost. The suitable of service principle which result from transaction cost such as the implementation of principle, accountable, leadership, productivity and service quality. In all of to see that the causal relation between variable have causal correlation in positive and significant with probability value (P) Â£ 0,05 and CR (t-value) Â³ 1,96.